The Influence of Islamic Education Curriculum Review on Teacher Commitment and Its Relevance to the History of Islamic Education - Ita Tryas Nur Rochbani; Miswanto Miswanto; Siti Jubaidah; Nurlatifah Nurlatifah (Universitas Hamzanwadi, 2025)
This study investigates the influence of Islamic Education (PAI) curriculum review, specifically curriculum understanding, implementation, and evaluation, on teacher commitment, while situating the findings within the historical trajectory of Islamic education. The study addresses ongoing concerns that PAI curricula have not fully responded to learners’ needs in the digital era, highlighting the importance of systematic curriculum review to sustain pedagogical relevance and professional engagement. Employing a quantitative approach with survey method, data were collected through a Likert-scale questionnaire administered to 120 PAI teachers from MAN 1 and MAN 2 Batam City, selected using simple random sampling. The data satisfied the normality assumption (p > 0.05), and the instrument demonstrated high reliability (Cronbach’s Alpha = 0.870). Multiple regression analysis reveals that curriculum understanding, implementation, and evaluation significantly influence teacher commitment (p < 0.05), with curriculum understanding emerging as the strongest predictor. The regression model explains 65% of the variance in teacher commitment (R² = 0.650). Interpreted from a historical perspective, these findings indicate that strengthening teachers’ conceptual mastery of the curriculum reinforces professional responsibility and instructional consistency, while enabling adaptation to contemporary educational demands without compromising core Islamic values. This study concludes that systematic PAI curriculum review not only enhances teacher commitment but also supports the continuity and resilience of Islamic education in modern learning contexts.